Business orientation, efficiency, and credit quality across business cycle: Islamic versus conventional banking. Are there any lessons for Europe and Baltic States?. Issue 1 (2nd January 2019) - Nosheen,; Rashid, Abdul
ABSTRACT: This paper empirically investigates the difference between Islamic and conventional banks in terms of business dynamics, cost structure, credit quality, and stability. It also examines the difference in the response of two types of banks during peak and trough phases of the business cycle. The analysis is carried out for a sample of 280 banks in 20 countries over the 1995–2014 period. The results reveal that Islamic banks are more involved in fee-based business, are less cost-efficient, have higher credit quality, and have higher capitalization than conventional banks. We also find that Islamic banks outperformed conventional banks with regard to their credit quality and stability indicators during the trough phase of the business cycle. The improved performance seems to be due to the differences in the provisioning strategies of the two types of banks, the non-aggressive lending profile of Islamic banks, and investment in real assets. Finally, based on the empirical findings, the paper also highlights potential lessons that conventional banks in Baltic States, which were severely hit by the 2007–2008 global financial crisis, can draw from Islamic banking principles.